Interactions among biological control, cultural control and barley resistance to the Russian wheat aphid, Diuraphis noxia (Kurdjumov), in Colorado, Kansas and Nebraska - Sotelo-Cardona, Paola Andrea (Kansas State University, 2010)
The Russian wheat aphid, Diuraphis noxia (Kurdjumov) (Hemiptera: Aphididae) (RWA), is an important pest in the U.S. Western Plains, causing hundreds of millions of dollars of losses to wheat and barley production through reduced yields and insecticide application costs. The objectives of this research were to evaluate the performance of two RWA-resistant barley varieties planted approximately one month earlier than normal in experimental fields at Fort Collins, Colorado; Tribune, Kansas; and Sidney, Nebraska during 2007, 2008, and 2009. The experimental design was a split-plot design with two main plot treatments (early and normal planting dates), and four split plot treatments (barley varieties) that were randomized within each main treatment plot. The varieties included two RWA-barley resistant varieties, Sidney and Stoneham, and the susceptible variety, Otis, under thiamethoxam-protected and unprotected regimes. Sampling of RWA, other cereal aphids, and natural enemy populations was conducted on four dates from mid May through early July. RWA populations collected from early-planted plots (first week of March) were significantly lower than normal-planted plots in 2007-2009 at the Fort Collins, Colorado and Tribune, Kansas sites. In samples collected from early planting date plots, RWA-resistant varieties yielded RWA populations similar to those found on the insecticide-treated susceptible variety at both Fort Collins and Tribune. At the Sidney, Nebraska site, very low RWA populations were present and there were no differences between either planting date or varietal treatments. The combined effect of early planting and RWA-resistant varieties reduced RWA populations at the Fort Collins, Colorado site in all three years. Results were similar at the Tribune, Kansas site in 2007, but differences due to planting date or variety were not observed in 2008 or 2009. The lowest RWA populations occurred at the Sidney, Nebraska site, were independent of planting date and varietal treatments. The RWA-resistant barley varieties had no negative impact on populations of other cereal aphids compared to those found on the susceptible variety, Otis at any of the three research sites. The only treatment effective in reducing other cereal aphids was the insecticide, thiamethoxam. There was also no clear response of populations of other cereal aphids to different planting date. Neither the RWA-resistant barley varieties nor the systemic, short residual action insecticide treatment had adverse affects on the abundance of natural enemies.
Keywords: Host plant resistance; Biological control; Cultural control; Integrated pest management; Russian wheat aphid; Barley; Agriculture, General (0473); Biology, Entomology (0353)